AN ANALYSIS OF STUDENTS’ SELF EFFICACY IN THE IMPLEMENTATION OF RECIPROCAL TEACHING IN READING - Andewi, Widi; Nagara, Erliza Septia (JLCEdu (Journal of Learning and Character Education), 2023)
This research explored the students’ perceptions of self-efficacy in reciprocal teaching. This research was descriptive qualitative research. The research participants of this research were XI MIA 1 class. The subjects were 11 representatives of the students as the interviewees. It was chosen based on observation, genre, and the score of the reading test. The data were taken from the observation and interview. The results showed language problems were the main aspects that influenced the students to have low self-efficacy while performing the four instructional strategies of reciprocal teaching. This suggests teachers should guide and control students in teaching reading process through reciprocal teaching because they play a prominent role in alleviating and controlling students’ self-efficacy.